THE AUTHORITY OF VILLAGE GOVERNMENT IN AFFIRMING BORDER MANAGEMENT (CASE STUDY OF GALANG ISLAND DISPUTE) - Yulianti, Rina; Permadi, Iwan (Brawijaya Law Journal, 2016)
Border Disputes related to territorial management between local Governments dominate the ongoing cases within the Ministry of Internal Affairs in Indonesia. This study aims to propose a model of a policy of border Disputes resolution using non-doctrinal legal research (socio-legal research). This research limited itself by looking at Galang Island, the which is disputed between the city of Gresik and Surabaya. To gain Appropriate analyzes, in depth interviews and secondary of data was conducted and collected both in Gresik and Surabaya. Furthermore, this research finds that the reason underpinned such Disputes lays on the weaknesses of village government in the territorial management proofing Formally they have been doing. It is submitted that in forming and affirming border delimitation, Indonesian Act Number 6 year 2014 on Village jo Ministry of Internal Affairs Regulation number 114 year 2014 can used as legal base.